2017
DOI: 10.1016/j.jns.2017.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive and behavioural impairment in amyotrophic lateral sclerosis: Frequency of abnormality and effect on survival

Abstract: Abstract:Objective: To screen for cognitive and behavioral impairment in people with amyotrophic lateral sclerosis (ALS) and controls with neuromuscular disease and to correlate these with clinical features. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 63 publications
5
26
0
Order By: Relevance
“…In addition, the levels in patients with cognitive impairment showed greater deviation from the healthy controls than those of patients without cognitive impairment, consistent with the suggestion that patients with cognitive impairment have more severe and widespread disease [269] . Between ALS with cognitive impairment and controls there was a significant difference in the expression of clusterin.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the levels in patients with cognitive impairment showed greater deviation from the healthy controls than those of patients without cognitive impairment, consistent with the suggestion that patients with cognitive impairment have more severe and widespread disease [269] . Between ALS with cognitive impairment and controls there was a significant difference in the expression of clusterin.…”
Section: Discussionsupporting
confidence: 85%
“…Because ALS is a heterogeneous disease, patients were subdivided on the basis of the presence of absence of cognitive impairment based on results of the ACE-III test. ALS participants with cognitive impairment measured with ACE-III had worse prognosis [239,269] , so this is a distinction that has clinical importance. Patients with cognitive impairment measured with these tools have more severe and widespread MRI changes [283] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients also vary in the presence or absence of cognitive impairment (Xu et al, 2017) and in the presence or absence of other non-motor issues .…”
Section: Clinical Correlates Of Hypermetabolism In Alsmentioning
confidence: 99%
“…Altered metabolism (Ahmed et al, 2014a) and changes in energy expenditure (Ahmed et al, 2016c) have been reported in patients with frontotemporal dementia (FTD). Cognitive impairment similar to that seen in FTD occurs in some ALS patients (Xu et al, 2017), and ALS and FTD appear to exist at opposite ends of a common disease spectrum (Ahmed et al, 2016a, De Silva et al, 2016. However, compared to patients with ALS, patients with FTD display a distinct metabolic profile, characterized by a higher BMI (Ahmed et al, 2014b) and altered eating patterns (Ahmed et al, 2016b).…”
Section: Potential Future Directionsmentioning
confidence: 99%